Migratory Behaviour of Birds Around The Pond At Village Choharian Wali, District Fazilka (Punjab). (International Journal of Food and Nutritional Sciences, 2022)
Ponds provides a high nutritional support for the birds to survive and breed. Presence offishes in the pond is one important factor resulting in selection of pond as habitat. Many birdsreside on and around these ponds and many are migratory. Bird migration occurs during theautumn every year from their places of breeding to their wintering places which arethousands of kilometres far- away. Migration means travelling for longer time at very longdistances, which may involve crossing certain barriers that may be mountains or rivers.(R.Wiltschko, 2003). Punjab has cold winters and hot summers. Birds are found at variousponds in Punjab region they exhibit distinct ecological behavioural patterns. One of the pondin Punjab is located in village Choharian wali, District Fazilka (Punjab). Migratory Behaviourof Birds at this pond was studied from September 2020 to March 2021.